The haematoma and its role in bone healing - Schell, H. (J Exp Orthop, 2017)
Fracture treatment is an old endeavour intended to promote bone healing and to also enable early loading and regain of function in the injured limb. However, in today’s clinical routine the healing potential of the initial fracture haematoma is still not fully recognized. The Arbeitsgemeinschaft für Osteosynthesefragen (AO) formed in Switzerland in 1956 formulated four AO principles of fracture treatment which are still valid today. Fracture treatment strategies have continued to evolve further, as for example the relatively new concept of minimally invasive plate osteosynthesis (MIPO). This MIPO treatment strategy harbours the benefit of an undisturbed original fracture haematoma that supports the healing process. The extent of the supportive effect of this haematoma for the bone healing process has not been considered in clinical practice so far. The rising importance of osteoimmunological aspects in bone healing supports the essential role of the initial haematoma as a source for inflammatory cells that release the cytokine pattern that directs cell recruitment towards the injured tissue. In reviewing the potential benefits of the fracture haematoma, the early development of angiogenic and osteogenic potentials within the haematoma are striking. Removing the haematoma during surgery could negatively influence the fracture healing process. In an ovine open tibial fracture model the haematoma was removed 4 or 7 days after injury and the bone that formed during the first two weeks of healing was significantly reduced in comparison with an undisturbed control. These findings indicate that whenever possible the original haematoma formed upon injury should be conserved during clinical fracture treatment to benefit from the inherent healing potential.